Serotonin system in the human placenta – the knowns and unknowns - Perić, Maja; Bečeheli, Ivona; Čičin-Šain, Lipa; Desoye, Gernot; Štefulj, Jasminka (Frontiers in Endocrinology, 2022)
The biogenic monoamine serotonin (5-hydroxytryptamine, 5-HT) is a chemical messenger widely distributed in the brain and various other organs. Its homeostasis is maintained by the coordinated activity of a variety of proteins, including enzymes of serotonin metabolism, transmembrane transporters of serotonin, and serotonin receptors. The serotonin system has been identified also in the placenta in rodent models as a key component of placental physiology. However, serotonin pathways in the human placenta are far from well understood. Their alterations may have long-lasting consequences for the fetus that can manifest later in life. In this review, we summarize information on the location of the components of the serotonin system in the human placenta, their regulation, function, and alterations in pathological pregnancies. We highlight current controversies and discuss important topics for future research.